On the Development of Parafoveal Preprocessing: Evidence from the Incremental Boundary Paradigm - Marx, Christina; Hutzler, Florian; Schuster, Sarah; Hawelka, Stefan (Frontiers in Psychology, 2016)
Parafoveal preprocessing of upcoming words and the resultant preview benefit are key aspects of fluent reading. Evidence on the development of parafoveal preprocessing during reading acquisition, however, is scarce. The present developmental (cross sectional) eye tracking study estimated the magnitude of parafoveal preprocessing of beginning readers with a novel variant of the classical boundary paradigm. Additionally, we assessed the association of parafoveal preprocessing with several reading related psychometric measures. Participants were children learning to read the regular German orthography with about one, three and five years of formal reading instruction (Grade 2, 4 and 6, respectively). We found evidence of parafoveal preprocessing in each Grade. However, an effective use of parafoveal information was related to the individual reading fluency of the participants (i.e., the reading rate expressed as words-per-minute) which substantially overlapped between the Grades. The size of the preview benefit was furthermore associated with the children’s performance on rapid naming tasks and with their performance on a pseudoword reading task. The latter task assessed the children’s efficiency of phonological decoding and our findings show that the best decoders exhibited the largest preview benefit.